2022
DOI: 10.1038/s41598-022-04809-8
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation increases beige fat differentiation and metabolic activity, preventing and treating obesity

Abstract: Beige and brown fat consume glucose and lipids to produce heat, using uncoupling protein 1 (UCP1). It is thought that full activation of brown adipose tissue (BAT) may increase total daily energy expenditure by 20%. Humans normally have more beige and potentially beige-able fat than brown fat. Strategies to increase beige fat differentiation and activation may be useful for the treatment of obesity and diabetes. Mice were fed chow or high-fat diet (HFD) with or without the iron chelator deferasirox. Animals fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Ferritin is the major iron storage protein complex, and the serum levels of ferritin are used to estimate body iron storage level, which is associated with the development of insulin resistance and metabolic syndrome [ 230 , 231 ]. In agreement, a recent report indicated that mice fed with an HFD and an iron chelator deferasirox exhibited protective effects against diet-induced obesity along with elevated energy expenditure and beige adipogenesis in WAT [ 232 ]. Genetic and pharmacological inhibition of these iron metabolic pathways in mitochondria induced obesity along with decreased energy expenditure [ 233 ].…”
Section: Obesity and Mitochondrial Metabolismsupporting
confidence: 75%
“…Ferritin is the major iron storage protein complex, and the serum levels of ferritin are used to estimate body iron storage level, which is associated with the development of insulin resistance and metabolic syndrome [ 230 , 231 ]. In agreement, a recent report indicated that mice fed with an HFD and an iron chelator deferasirox exhibited protective effects against diet-induced obesity along with elevated energy expenditure and beige adipogenesis in WAT [ 232 ]. Genetic and pharmacological inhibition of these iron metabolic pathways in mitochondria induced obesity along with decreased energy expenditure [ 233 ].…”
Section: Obesity and Mitochondrial Metabolismsupporting
confidence: 75%
“…Taken together, our data point to an anti‐adiposity effect of PHZ in hypothalamic obese animals, corroborating recently published data showing that iron chelation increases beige fat differentiation and prevents obesity (Nazari et al., 2022). Interestingly, a reduction in visceral WAT depots was not observed in MSG PHZ rats, suggesting that this lipolytic action is limited to BAT and subcutaneous WAT.…”
Section: Discussionsupporting
confidence: 92%
“…showing that iron chelation increases beige fat differentiation and prevents obesity (Nazari et al, 2022). Interestingly, a reduction in visceral WAT depots was not observed in MSG PHZ rats, suggesting that this lipolytic action is limited to BAT and subcutaneous WAT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Nazari et al confirmed the effects of iron chelators on adipose tissue, demonstrating that DFX is able to activate beige fat differentiation and metabolic activity, thus suggesting it as a potential therapeutic strategy to treat obesity and to prevent its metabolic complications. Interestingly, in C57Bl/6 mice, placed on high-fat diet and treated or not with DFX, they analyzed the inguinal fat, a classically brown or beige fat store in mice, observing an increase in UCP1 positive cells after DFX administration [ 94 ].…”
Section: Iron Chelators As Anti-inflammatory Drugsmentioning
confidence: 99%